Rancang Bangun dan Analisis Akurasi Dinamometer Untuk Kajian Biomekanika Gaya Penari Bapang - Prasetyo Adri Pamungkas; Muhammad Agus Sahbana; Nurida Finahari (Virtual of Mechanical Engineering Article, 2020)
Biomechanics is the study of internal and external forces acting on the body of living things and the effects of these forces. The study of the motion of living things is carried out by applying theories and laws of motion. The forces acting on the human body organ systems in biomechanics include gravitational force, body reaction force and muscle force. These forces can be measured using a dynamometer. This study aims to design a load cell sensor-based dynamometer which is used as a mass sensor, applied to the design, then analyzed its accuracy for the study of the biomechanics of Bapang dancers. The design is based on the availability of research funds but refers to the Mettler Toledo weighing principle, where the floor scale is designed as a measuring base for the dancers to perform their dances. The area of ​​this measuring base is predefined as 1.25 x 1.25 m. This has reduced the accuracy of the design results considering the ideal area for free dancing is 3 x 3 m. The design results have worked well and can record changes in the load during changes in dancer movements. The measured reading accuracy value reaches 98.36% but still includes measurement errors due to differences in the place and time of the calibration measurement, and differences in the clothes of the people who are the object of the load. The load reading display captures an average time delay of 0.468 seconds. It is recommended that the drawbacks of this design be corrected by designing a dancer's load measurement system using a load sensor that is shaped like a ballet shoe, but uses a wireless data transfer system so that the dancers can move freely. In addition, the shoe-shaped dynamometer design can definitively separate the load readings for the right and left feet.